The Effect of Work Environment, Work Discipline and Human Resource Information System on Employee Performance at PT Nasmoco Bahtera Motor Mlati, Sleman, Yogyakarta - Mazen Haqi Permana; Hafid Kholidi Hadi (Universitas Negeri Surabaya, 2025)
The purpose of this study is to ascertain whether the work environment, work discipline, and human resource information system (HRIS) have an impact on employee performance. The PT Nasmoco Bahtera Motor branch in Mlati, Sleman, Yogyakarta, is the focus of this study. A total of 85 respondents were gathered through both online and offline questionnaire. With the help of SPSS version 20, this quantitative study employs multiple linear regression analysis approaches. The findings show that work discipline significantly affects employee performance, that the work environment has no effect on employee performance, that HRIS has significantly effect on employee performance, and that the combination of work discipline, work environment and HRIS significantly affects employee performance.